Gene action, heterosis and inbreeding depression of yield characters in mutant lines of upland cotton - Bertini, Cândida Hermínia Campos de Magalhães; Silva, Fanuel Perreira da; Nunes, Raimundo de Pontes; Santos, José Higino Ribeiro dos (Pesquisa Agropecuaria Brasileira, 2001)
The objective of this study was to estimate the heredity parameters in hybrids of upland cotton (Gossypium hirsutum L.) obtained from a conventional genetic analysis involving two parental lines and including the F1, F2, RC1, and RC2 generations. The gene action, heterosis and inbreeding depression were calculated for the characters days to first flower initiation, number of bolls, boll weight, fiber percent, fiber yield and weight of 100 seeds. Narrow-sense heritability ranged from 2.27% for boll weight to 67.57% for fiber percent. The dominance effect was the most important to days to first flower initiation, number of bolls, boll weight, and fiber yield, while the additive effect was the most important for fiber percent and weight of 100 seeds. Heterotic effects of 96.41% was obtained for fiber yield and of -0.77% for days to first flower initiation. Inbreeding depression was detected only for boll weight and fiber percent. The presence of large amount of additive effects suggests that there is a potential for obtaining further yield gains and fiber property improvements without resorting to the use of hybrids. On the other hand, significant dominance deviations indicated that breeding for hybrids varieties would result in improvement over existing ones.